Chirurgische Therapie intraduktaler papillär muzinöser Neoplasien des Pankreas - Fritz, Stefan; Büchler, Markus W.; Werner, Jens (Der Chirurg, 2012)
Intraductal papillary mucinous neoplasms (IPMN) of the pancreas constitute an increasingly recognized entity of cystic pancreatic tumors which are characterized by mucin production and epithelial growth within the pancreatic ducts and show a wide spectrum of morphologic variants. They may arise in the main pancreatic duct, its major side branches or in both (mixed type). Furthermore, IPMNs are considered as precursor lesions to pancreatic adenocarcinoma. However, it is not clear what the time course of such potential neoplastic transformation might be and whether all lesions progress to malignant tumors. As currently no diagnostic test can reliably differentiate between benign and malignant tumors the majority of newly diagnosed IPMNs should be surgically resected. According to current treatment guidelines (Sendai criteria), only asymptomatic side branch IPMNs of less than 3 cm in diameter without suspicious radiologic features, such as nodules, thickness of the cystic wall or size progression, should be treated conservatively without the need for surgical resection. Recently, this approach has become controversial due to a relevant number of reported Sendai negative IPMNs which revealed malignant transformation on final histological examination. The focus of this review is on the surgical treatment of IPMNs with regard to the current state of knowledge.